Analisis Kegagalan Pada Roda Gigi Miring Intermediate Gear 2 Pada Gear Box Untuk Roller Press Milling Machine - Andri Anto; Dedison Gasni (Department of Mechanical Engineering, Universitas Andalas, 2017)
This paper reports the result of an investigation of a fatigue failure of a helical gear in a reducer gear box used in roller press milling machine. Standard procedures in stress analysis on helical gear were used in failure analysis of this helical gear. It was found that the gear failed by fatigue fracture. Beach marks on the fracture surfaces were clearly visible. Detail examination of the surface of the gear revealed that extensive surface damage had occurred in the form of pitting and scuffing. Sub-surface damages in the form of spalling were also observed. Such observations indicated that the gear was under excessive contact stress during operation. Stress analysis did, in fact, confirm such hypothesis. Stress analysis has been conducted by using Niemann methods and Lewis equation. Finite element methods also have been conducted by using commercial software where the stress was obtained on the root of gear by modeling with pitting, without pitting, and matting. The results show that the working stresses on the root of gear were lower than strenght of gear material. It was proofed that the gear failure due to dynamic loading but not because of static loading. These surface and sub-surface damages leed to fatigue crack initiation followed by crack growth and eventual fracture excessive contact stress. It is showed that from contact mechanic analysis showed that Hertzian stress and shear stress at surface and at sub surface were excessive. It is concluded that the helical gear failed by fatigue fracture initiated by surface and sub-surface damages resulting from excessive contact stress.